PENENTUAN LAJU REAKSI MAKSIMAL (Vmaks) DAN KONSTANTA MICHAELIS-MENTEN (KM) ENZIM LIPASE PANKREAS PADA SUBSTRAT MINYAK KELAPA, MINYAK SAWIT, DAN MINYAK ZAITUN - Ratnayani, Ketut; Mayun Laksmiwati, A. A. I. A.; Sudiarto, Maman (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015DO - 10.24843/JCHEM.2015.v09.i01.p15, 2015)
A main element in the Michaelis-Menten equation is K m , which is typical for a particular enzyme, with a specific substrate at a certain pH and temperature conditions. The aim of this study is determining the difference in the maximum rates (V max ) and Michaelis-Menten constant (K m ) of pancreatic lipase on the coconut oil, palm oil, and olive oil substrates and the most effective hydrolysis by the pancreatic lipases. K m value was calculated by measuring the rate of the catalyzed hydrolysis with various concentrations of pH, temperature, and the optimum incubation time. Before calculating the value of Vmax and Km, the initial rate (v 0 ) was calculated with the titrimetric method. The results showed that V max was  2,11 × 10 -3 mmol/min on coconut oil substrate; 2,30 × 10 -3 mmol/min on palm oil substrates; and 1,60 × 10 -3 mmol/minutes on olive oil substrate. While the pancreatic lipase K m values ??were 1,21 × 10 4 ppm on coconut oil; 2,29 × 10 4 ppm on palm oil; and 1,60 × 10 4 ppm on the olive oil. This results suggested the pancreatic lipase catalyzed the hydrolysis was most effective on coconut oil compared with palm oil and olive oil.
Keywords: pancreatic lipase, coconut oil, palm oil, olive oil